The Impact of Physical and Psychological Job Demands on Nurses’ Work-Related Low Back Pain: A Systematic Review and Meta-analysis - Zoelfigar Mohamed; Malek Al-Natour (International Journal of Occupational Safety and Health)
Introduction: In spite of the important advancement in methods and tools associated with nurses’ Work-Related Lower Back Pain (WrLBP) prevention and treatment, there is still poor worldwide understanding of the phenomena of nurses’ WrLBP with high prevalence, therefore, the aim of the current review is to evaluate the significant predictors of nurses’ WrLBP (i.e. physical job demands, psychological job demands).